Inflammation, oxidative stress and gene expression: the postprandial approach in professional soccer players to reduce the risk of muscle injuries and early artherosclerosis - Perrone, M. A.; Donatucci, B.; Salvati, A.; Gualtieri, P.; de Lorenzo, A.; Romeo, F.; Bernardini, S. (Medicina dello Sport, 2019)
BACKGROUND: Recent studies have shown that inflammation and oxidative stress contribute to muscle injuries and early atherosclerosis in athletes. European Food Safety Authority (EFSA) scientific opinion has acknowledged the hydroxytyrosol (3,4 dihydroxyphenylethanol [3,4-DHPEA or HT]) and derivatives, contained in extra virgin olive oil, typically used in Mediterranean diet may play a crucial role in the reduction of the inflammatory pathway. The aim of the study was to determine the effect of 25 g of phenols-rich extra virgin olive oil (p-EVOO) in professional soccer players. METHODS: The clinical study was a randomized, controlled trial to determine the acute effect in the postprandial time of 25g of p-EVOO. Twenty-two professional soccer players of an Italian Serie A team resulted eligible for the study. We evaluated plasma metabolites, oxidative stress biomarkers and gene expression of 8 genes related to oxidative stress and human inflammasome pathways, lasting two hours after p-EVOO administration. RESULTS: A significant reduction of oxidized low-density lipoprotein (oxLDL) and malondialdehyde (MDA) was observed (P<0.05), alongside a significant up-regulation of catalase (CAT), superoxide dismutase 1 (SOD1), and upstream transcription factor 1 (USF1) (P<0.05). CONCLUSIONS: This study shows that the intake of 25 g of p-EVOO was able to modulate, in postprandial time, the antioxidant profile and the expression of inflammation and of the oxidative stress-related genes, such as SOD1, USF1 and CAT. We also observed a significant reduction of MDA and oxLDL, plasma metabolites of oxidative stress. Our data show that the postprandial intake of phenols and antioxidants can reduce the inflammatory pathway and oxidative stress and therefore the risk of muscle injuries and early atherosclerosis in professional soccer players. More studies on a larger population are necessary before definitive conclusions can be draw.